The Meaning of Qiwamah in the Qur'an: The perspective of Khaled M. Abou El-Fadl - Ibrahim Hanif Nasution; Ghita Kinanti Pratiwi; Aisyah Simamora (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This research aims to focus on how to understand the meaning of Qiwamah in the Qur'an through an idea from the hermeneutic reading of the negociating process. Negotiative hermeneutics is oriented towards the authority of Islamic law, where a meaning is the result of interactions that are assembled between the author, the text, and the reader. Negotiative hermeneutics aims to limit the authoritarianism of the reader so as not to eliminate the authority of the text. Therefore, in an effort to avoid this authoritarian attitude, an Islamic figure from Kuwait, Khaled M. Abou El-Fadl makes five prerequisites that must be met by readers, including; honesty, sincerity, wholeness, rationality and self-control. The description of this research is in the form of an analysis of a verse (content analysis) and is included in library research, namely collecting data related to research. This study uses the wrong view. At the end of this research, the researcher analyzes that there is a contextual understanding in understanding the meaning of Qiwamah which in general among mufassirin understands Qiwamah textually, as it is defined as a leader, guardian, protector and so on.